1984
DOI: 10.1093/schbul/10.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Information Processing and Attentional Functioning in the Developmental Course of Schizophrenic Disorders

Abstract: This article examines the evidence that certain deficits in information processing and attentional functioning are present across populations at risk for schizophrenic disorder, with active schizophrenic psychotic symptomatology, and in relative remission after a schizophrenic psychosis. In addition, the evidence that some deficits in processing information occur only in the actively psychotic period is inspected. Deficits in vigilance tasks with high-processing loads, in forced-choice span of apprehension for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
600
3
6

Year Published

1986
1986
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,139 publications
(651 citation statements)
references
References 186 publications
42
600
3
6
Order By: Relevance
“…This finding supports the general concept that deficits in early pre-attentive information processing may underlie the more complex attentional and cognitive abnormalities in psychotic states such as schizophrenia (McGhie and Chapman, 1961;Nuechterlein and Dawson, 1984;Nuechterlein et al, 1994). Specifically, it is thought that schizophrenia patients suffer from a form of sensory inundation related to attentional deficits that are caused by a general inability to filter external intrusive stimuli and thereby focus on important and information-laden aspects of the environment (Braff et al, 1978Nuechterlein and Dawson, 1984;Geyer and Braff, 1987). Along this line of argument, there is to date only one study that directly demonstrated that PPI deficits in schizophrenia subjects are correlated with distractibility in a continuous performance task and with lateralized attention on the Posner test (Karper et al, 1996).…”
Section: Discussionsupporting
confidence: 85%
“…This finding supports the general concept that deficits in early pre-attentive information processing may underlie the more complex attentional and cognitive abnormalities in psychotic states such as schizophrenia (McGhie and Chapman, 1961;Nuechterlein and Dawson, 1984;Nuechterlein et al, 1994). Specifically, it is thought that schizophrenia patients suffer from a form of sensory inundation related to attentional deficits that are caused by a general inability to filter external intrusive stimuli and thereby focus on important and information-laden aspects of the environment (Braff et al, 1978Nuechterlein and Dawson, 1984;Geyer and Braff, 1987). Along this line of argument, there is to date only one study that directly demonstrated that PPI deficits in schizophrenia subjects are correlated with distractibility in a continuous performance task and with lateralized attention on the Posner test (Karper et al, 1996).…”
Section: Discussionsupporting
confidence: 85%
“…Frontal lobe patients are known to produce uncontrolled behaviors imitating simple actions that other individuals perform in their presence (L'Hermitte et al 1972). Frontal lobe pathology has been documented in schizophrenia (Jeste et al 1996;Weinberger et al 1986), and flawed frontal gating mechanisms have been hypothetically associated to the perceptual and information-processing deficits seen in this condition (Braff et al 1995;Nuechterlein and Dawson 1984). Schizophrenic patients show motor abnormalities such as grimacing, echopraxia, posturing, stereotypy, echolalia and others in speech production , which could be the result of prefrontal gating failures.…”
Section: Discussionmentioning
confidence: 99%
“…The mirror-like premotor and motor increased compensatory activity we describe here could be facilitated by such a prefrontal deficit, particularly when processing of facial affect information relevant for social functioning is required that demands additional resources. Patients with schizophrenia exhibit a number of sensory and perceptual processing deficits (Braff et al 1995;Nuechterlein and Dawson 1984) likely contrib-uting to prefrontal-based perception-action cycle abnormalities. Among those, deficits specifically related to facial affect discrimination may involve cerebral sensory systems such as the superior temporal sulcus, the fusiform gyrus, and the inferior frontal cortex, as some studies indicate (Hariri et al 1999;Nakamura et al 1999;Haxby et al 2000;Allison et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Attention/vigilance was assessed using a Continuous Performance Test (CPT‐HQ) with working memory (WM) load, also known as CPT‐AX (Nuechterlein and Dawson 1984) (longer reaction times reflecting worse performance). The Wechsler Adult Intelligence Scale (WAIS)‐III (Wechsler 1997) subtest Arithmetic was used to measure WM, which addresses both verbal comprehension and arithmetic skills.…”
Section: Methodsmentioning
confidence: 99%